Corporate Digital Transformation and ESG Performance - Evidence from Chinese Listed Companies - Xiong, Junzhe (Transactions on Economics, Business and Management Research, 2024)
Corporate digital transformation provides conditions to stimulate the endogenous motivation of corporate ESG performance by helping enterprises optimize the allocation of innovation resources and reduce financing costs. This paper empirically examines the impact and mechanism of corporate digital transformation on corporate ESG performance using A-share listed companies in Shanghai and Shenzhen from 2011 to 2022 as the research sample. It is found that digital transformation significantly improves the ESG performance of enterprises and still holds after a series of robustness tests and endogeneity treatment. The results of this paper enrich the research on the economic consequences of digital transformation for real enterprises and the influencing factors of enterprises’ ESG performance, which are of great revelation and reference value for promoting the digital transformation of real enterprises and constructing a new pattern of digital economy.